Development of Y-TZP/MWCNT-SiO2 nanocomposite for dental protheses - da Silva, Lucas Hian; Rinaldi, Laura Ajamil; Lazar, Dolores Ribeiro Ricci; Ussui, Valter; Tango, Rubens Nisie; Belli, Renan; Lohbauer, Ulrich; Cesar, Paulo Francisco (Journal of the Mechanical Behavior of Biomedical Materials, 2023)
Y-TZP/MWCNT-SiO2 nanocomposite was synthesized by co-precipitation and hydrothermal treatment methods. After the characterization of the MWCNT-SiO2 powder, specimens were obtained from the synthesized material Y-TZP/MWCNT-SiO2 by uniaxial pressing for a second characterization and later comparison of its optical and mechanical properties with the conventional Y-TZP. The MWCNT-SiO2 was presented in bundles of carbon nanotubes coated by silica (mean length: 5.10 ± 1.34 μm /D90: 6.9 μm). The composite manufactured was opaque (contrast ratio: 0.9929 ± 0.0012) and had a white color with a slightly difference from the conventional Y-TZP (ΔE00: 4.4 ± 2.2) color. The mechanical properties of Y-TZP/MWCNT-SiO2: vickers hardness (10.14 ± 1.27 GPa; p = 0.25) and fracture toughness (4.98 ± 0.30 MPa m1/2; p = 0.39), showed no significant difference from the conventional Y-TZP (hardness: 8.87 ± 0.89; fracture toughness: 4.98 ± 0.30 MPa m1/2). However, for flexural strength (p = 0.003), a lower value was obtained for Y-TZP/MWCNT-SiO2 (299.4 ± 30.5 MPa) when compared to the control Y-TZP (623.7 ± 108.8 MPa). The manufactured Y-TZP/MWCNT-SiO2 composite presented satisfactory optical properties, however the co-precipitation and hydrothermal treatment methods need to be optimized to avoid the formation of porosities and strong agglomerates, both from Y-TZP particles and MWCNT-SiO2 bundles, which lead to a significant decrease in the material flexural strength.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Co-precipitation of mixed hydroxides; Hydrothermal treatment; Multi-walled carbon nanotube; Yttria-stabilized tetragonal zirconia polycrystals